Rare Etiology of Acute Embolic Stroke in a 17-Year-Old Girl: Cardiac Papillary Fibroelastoma - Chadha, Tanya; Cooke, Susan; Shillingford, Michael S.; Ceithaml, Eric (Journal of Pediatric Intensive Care, 2018)
A cardiac papillary fibroelastoma is a benign, pedunculated tumor with strand-like projections arising from the endocardium. While often discovered incidentally, these tumors can embolize resulting in major neurologic events. There is a dearth of pediatric literature describing the necessity and optimal timing of surgical intervention for this rare primary cardiac tumor after a cerebrovascular event. We report an interesting case and the subsequent management dilemma in a teenage patient presenting with acute embolic strokes secondary to an aortic valve papillary fibroelastoma. Despite its rarity, a high index of suspicion should be maintained for such tumors in previously healthy children presenting with acute stroke.
Keywords: pediatric; stroke; cardiac tumor